2020
DOI: 10.5149/northcarolina/9781469654973.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

From Here to Equality

Abstract: Racism and discrimination have choked economic opportunity for African Americans at nearly every turn. At several historic moments, the trajectory of racial inequality could have been altered dramatically. Perhaps no moment was more opportune than the early days of Reconstruction, when the U.S. government temporarily implemented a major redistribution of land from former slaveholders to the newly emancipated enslaved. But neither Reconstruction nor the New Deal nor the civil rights struggle led to an economica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…We are not interpreting any of the decomposed effects in isolation as what would actually happen if we were to somehow equalize black-white exposures or effects of exposures. But we agree with arguments made by Robinson and Bailey (2020) that precise quantitative identification of such hypothetical future causal effects is not a prerequisite for supporting a broad policy agenda aimed at dismantling pathways of structural racism affecting health, an agenda based on retrospective quantitative and qualitative causal triangulation, a robust theory of racism, and longstanding social movements (Bailey et al 2017;Darity and Mullen 2020;Ford and Airhihenbuwa 2010;Taylor 2016).…”
Section: Scope and Limitationssupporting
confidence: 74%
“…We are not interpreting any of the decomposed effects in isolation as what would actually happen if we were to somehow equalize black-white exposures or effects of exposures. But we agree with arguments made by Robinson and Bailey (2020) that precise quantitative identification of such hypothetical future causal effects is not a prerequisite for supporting a broad policy agenda aimed at dismantling pathways of structural racism affecting health, an agenda based on retrospective quantitative and qualitative causal triangulation, a robust theory of racism, and longstanding social movements (Bailey et al 2017;Darity and Mullen 2020;Ford and Airhihenbuwa 2010;Taylor 2016).…”
Section: Scope and Limitationssupporting
confidence: 74%
“…Although analyses of wealth shocks or other quasi-experimental variation might support a causal relationship, such analyses may fail to capture the effects of overall racial wealth inequities, which are largely inherited (eg, through the inheritance of property or educational opportunity), reflecting the long-term effects of structural racism. 7 , 12 , 14 , 21 , 23 , 24 , 42 Because our interest was in capturing the consequences of historically mediated wealth gaps, we opted for a more associational approach. We note that our approach, by focusing on wealth at baseline, addresses (at least in part) concerns related to reverse causality (ie, that robust health facilitates asset accumulation).…”
Section: Discussionmentioning
confidence: 99%
“…22 Craemer et al 12 have suggested figures as high as $300 million per person, based on the value of lost freedom, wages, and assets, with compound interest. Darity and Mullen 23 have advocated closing the mean pretax wealth gap via payments of approximately $800 000 per Black household.…”
Section: Methodsmentioning
confidence: 99%
“…This plays out in many existing massive-scale reparative projects; for instance, federal reparations programs for human rights violations in Argentina, Chile, and El Salvador, reparations for Japanese internment in the US, and reparations by the German government for Holocaust war crimes all provide recourse to victims and families of a specific historical atrocity (De Greiff, 2008). In the case of US reparations to Black Americans, Darity details an economic history of injustice, from exploitation through slavery to Jim Crow era discrimination to present-day inequities in the wealth gap (Darity and Mullen, 2020). Darity proposes sending an itemized reparations bill to the US government and to institutions that have benefited and continue to benefit from racial injustice, and he also suggests non-economic compensation in the form of education and apology.…”
Section: Reparations As Redress and Accountabilitymentioning
confidence: 99%